2015
DOI: 10.1007/s11060-015-1977-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of brain metastases in patients with metastatic melanoma while receiving ipilimumab

Abstract: To assess the development of brain metastases under ipilimumab and identify clinical, histological or evolving criteria related to the appearance of these metastases. A retrospective study was conducted in 52 patients treated with 4 cycles of ipilimumab 3 mg/kg every 3 weeks for unresectable stage III or stage IV melanoma between January 2011 and July 2013 in a Department of Dermato-Oncology. As no data has been find in the literature, the results were compared to our other cohort of patients treated with vemu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…This appears particularly relevant in the context of immune cell activity against extravasated single cancer cells and micrometastases when the normal brain parenchyma, including the blood-brain barrier, is still largely intact. In line with this concept, melanoma patients developed remarkable high rates of BM during Ipilimumab in one study (57), which fits to the empirical impression of many clinical experts in the field. In contrast, brain macrometastases have been found to respond well to ipilimumab and other immune checkpoint inhibitors in subsets of patients (35,58) which supports the general concept that preventing metastatic outgrowth is very different (biologically and therapeutically) from targeting large established macrometastases.…”
Section: Discussionsupporting
confidence: 78%
“…This appears particularly relevant in the context of immune cell activity against extravasated single cancer cells and micrometastases when the normal brain parenchyma, including the blood-brain barrier, is still largely intact. In line with this concept, melanoma patients developed remarkable high rates of BM during Ipilimumab in one study (57), which fits to the empirical impression of many clinical experts in the field. In contrast, brain macrometastases have been found to respond well to ipilimumab and other immune checkpoint inhibitors in subsets of patients (35,58) which supports the general concept that preventing metastatic outgrowth is very different (biologically and therapeutically) from targeting large established macrometastases.…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, depending on blood–brain barrier penetrance and other relevant factors, the incidence of MBMs might actually decrease. The CNS has been identified as a common first site of systemic treatment failure in patients with melanoma treated with FDA‐approved targeted therapies, but has yet to be characterized in depth in patients treated with immunotherapies (Frenard et al., ; Kim et al., ). In addition, it is probable that these new therapies will impact the outcomes in patients with MBM, based on the results from initial prospective clinical studies (Long et al., ; Margolin et al., ).…”
Section: Introduction: Clinical Features and Outcomes Of Melanoma Cenmentioning
confidence: 99%
“…Clinical trials have proven the efficacy of ipilimumab (the CTLA-4 inhibitor), with reported central nervous system control rates of 16–65% and median OS times of 2.5 to 29.3 months, grade 3 to 4 toxicity was 6 to 44.7% (Table 2 ). [ 8 20 ] However, few trials have specifically studied the activity of anti-PD1 drugs in MBM patients. Some researchers have explored the efficacy of Pembrolizumab in MBM patients, the outcome seemed optimistic combined with radiotherapy (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%